Fluorescent cellulose-based hydrogel with double functions of heavy metal adsorption and detection and application of fluorescent cellulose-based hydrogel
By preparing a bifunctional fluorescent cellulose-based hydrogel containing fluorescent probes and nanocellulose for heavy metal adsorption and detection, the problem of heavy metal removal and detection in traditional methods has been solved, achieving efficient and economical heavy metal treatment and selective detection.
Patent Information
- Application Number
- CN202411226175.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2024-12-13
AI Technical Summary
Existing technologies are insufficient for the efficient removal and selective detection of heavy metal ions Cr(VI) in water. Traditional methods are cumbersome and susceptible to interference, traditional cellulose-based hydrogels lack detection capabilities, and the preparation of highly adsorbent materials is expensive and polluting.
A bifunctional fluorescent cellulose-based hydrogel for heavy metal adsorption and detection was developed, comprising 0.62%-0.72% fluorescent probe, 0.05%-0.2% nanocellulose and the balance acrylic hydrogel. Nanocellulose was prepared by TEMPO oxidation and combined with the fluorescent probe to form a three-dimensional network structure, thereby achieving adsorption and fluorescence detection of Cu(II) and Cr(VI).
It achieves efficient adsorption and selective detection of Cu(II) and Cr(VI), reduces the detection limit, improves the ease of operation and anti-interference ability, and provides an economical and efficient heavy metal treatment solution.
Smart Images

Figure CN119119666A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer composite materials, and in particular to a heavy metal adsorption and detection dual-function fluorescent cellulose-based hydrogel and its application. Background Art
[0002] With the continuous development of global industrialization, heavy metals are increasingly used in various fields. Heavy metal ions such as Cr(VI) and Cu(II) inevitably enter the ecosystem, causing serious environmental damage. Even at low concentrations, these metals can accumulate in the food chain, posing a serious threat to human health and causing acute poisoning. Therefore, the effective removal of metal ions in water is a very important concern today. Commonly used techniques include chemical precipitation, coagulation, membrane filtration, electrodialysis, ion exchange and adsorption. Due to its convenience and high removal efficiency, adsorption has become the most commonly used technology for removing heavy metal ions. Commonly used adsorbents such as biochar, biochar, ion exchange resins and hydrogels have recently been developed for treating heavy metal ion pollution in wastewater. Especially Cr(VI), which is 100 times more toxic than Cr(III). In traditional atomic spectroscopy analysis, only the total chromium content (without distinguishing between Cr(III) and Cr(VI)) can be measured, but it is not possible to conveniently and quickly selectively determine Cr(VI) with higher toxicity and lower limit. Therefore, in environmental sewage, the treatment and selective detection of heavy metal Cr(VI) have always been a pain point and difficulty in the fields of environment, food, etc. The national standard (GB / T 7467) uses diphenylcarbazide spectrophotometry to selectively determine heavy metal Cr(VI), but in the actual determination process, this method has many disadvantages: (1) derivatization is required, the operation is cumbersome, and the uncertainty increases; (2) the anti-interference ability is poor, because the spectrophotometry method will be interfered by other ultraviolet absorbing substances in the test solution, and heavy metals often have multiple elements mixed together. Iron ions exceeding 1 mg / L will greatly interfere with the determination of Cr(VI). Therefore, this method can only determine some relatively simple matrix samples. Complex matrices have high requirements for pretreatment and cannot even be accurately determined.
[0003] Hydrogel is a chemically or physically cross-linked hydrophilic polymer with a three-dimensional network structure that can swell but does not dissolve in water. It is a promising heavy metal ion adsorbent. In addition, since hydrogel can effectively adsorb heavy metal ions in water and can be easily separated from wastewater after adsorption, thus preventing secondary pollution, this special property has attracted widespread attention in the field of heavy metal adsorption. In order to further improve the adsorption performance of hydrogels, highly adsorbent materials (such as silica, graphene, etc.) are often introduced into adsorbent hydrogels. However, the preparation of highly adsorbent materials is usually expensive and polluting. Therefore, the development of economical, efficient and environmentally friendly high-efficiency adsorbent materials has important practical application value.
[0004] Carboxylated cellulose-based adsorbents have several advantages, including their abundant raw material availability, cost-effectiveness, and biodegradability. Carboxylated cellulose is an ideal material for adsorption applications due to its large specific surface area and abundant hydroxyl groups. However, conventional cellulose-based hydrogels do not have the ability to detect heavy metal ions. For the detection of heavy metal ions, specialized spectroscopic techniques such as absorption spectroscopy, UV-visible spectroscopy, inductively coupled plasma mass spectrometry, atomic emission spectroscopy, etc. have been traditionally used. These traditional methods have high sensitivity and selectivity in detection, but face challenges in sample preparation, long-distance transportation, and require trained personnel to operate the instruments. The development of fluorescent materials has opened up new possibilities for the detection of heavy metal ions in wastewater. Fluorescence technology has had a significant impact on metal sensors due to its non-invasive detection process and high sensitivity. By exploiting the changes in the internal electronic structure of the host molecule, fluorescent sensing materials can provide sensitive optical signals when interacting with guest molecules (metal ions). This is widely used in the detection of metal ions in solution. Various organic, inorganic, and hybrid compounds, as well as nanocomposites, have been used to develop sensitive and selective sensors. Although there are an increasing number of fluorescent probes for the detection of heavy metal ions, few fluorescent probes have been incorporated into cellulose hydrogels for the detection and removal of heavy metal ions. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a dual-functional fluorescent cellulose-based hydrogel for heavy metal adsorption and detection, which realizes efficient adsorption and detection of Cu(II) and Cr(VI). Due to its simultaneous adsorption and enrichment, and quantitative fluorescence detection effect, trace heavy metals in water samples can be first adsorbed into the hydrogel for enrichment, and have a good fluorescence effect after complexing with the probe, so that they can be efficiently measured, which has great potential for treating harmful metals in wastewater.
[0006] The technical solution adopted by the present invention to solve the technical problem is: a heavy metal adsorption and detection dual-function fluorescent cellulose-based hydrogel, which contains 0.62%-0.72% of fluorescent probe, 0.05%-0.2% of nanocellulose, and the remainder of acrylic acid hydrogel in terms of mass percentage;
[0007] Among them, the structural formula of the fluorescent probe is:
[0008]
[0009] The nanocellulose is TEMPO-oxidized nanocellulose.
[0010] Furthermore, the fluorescent probe is prepared according to the following steps:
[0011] A1, dissolving 4-dimethylaminopyridine in tetrahydrofuran, and then adding diethyl iminodiacetate;
[0012] A2, dissolving dansyl chloride in ethyl acetate, and then adding the whole to the solution obtained in step S1, stirring and reacting at room temperature for about 12-18 hours; wherein the mass ratio of dansyl chloride, diethyl iminodiacetate and 4-dimethylaminopyridine is 1:(0.67-0.78):(0.61-0.72);
[0013] A3, quenching the reaction, separating and purifying to obtain an intermediate compound;
[0014] A4. Add the intermediate compound to ethanol, and gradually add sodium hydroxide aqueous solution dropwise at 50-60°C with stirring; the color of the mixture changes from yellow to red and finally to dark red; remove the ethanol, and then acidify with hydrochloric acid solution until the pH is about 3, filter, and dry the obtained solid to complete the preparation of the fluorescent probe; wherein the molar ratio of the intermediate compound to sodium hydroxide is 1:(8-12).
[0015] Furthermore, the reaction quenching in step A3 is performed by adding a saturated aqueous solution of ammonium chloride to quench the reaction.
[0016] Furthermore, the separation operation of step A3 is: separating the organic phase and extracting the aqueous phase with ethyl acetate; combining the organic phases, drying the organic phases, and concentrating under reduced pressure; the purification operation of step A3 is: using flash silica gel column chromatography, and its mobile phase is a mixture of ethyl acetate and n-hexane in a volume ratio of 1:3.
[0017] Furthermore, the fluorescent cellulose-based hydrogel is prepared according to the following steps:
[0018] B1. Add nanocellulose to sodium hydroxide solution for uniform dispersion, then add acrylic acid monomer, crosslinking agent, initiator and fluorescent probe, and stir to react for 1.5-2.5h; wherein the mass ratio of acrylic acid monomer, crosslinking agent and initiator is 1:(0.007-0.012):(0.14-0.16);
[0019] B2. Then, pour the mixed solution into a mold and react at 50-65° C. for 2.5-3.5 hours. Immerse the reaction product in distilled water to remove residual reagents, thereby obtaining a fluorescent cellulose-based hydrogel.
[0020] Furthermore, the cross-linking agent is N,N'-methylenebisacrylamide.
[0021] Furthermore, the initiator is 2,2'-azobisisobutylamidine dihydrochloride.
[0022] Furthermore, the nanocellulose is prepared according to the following steps:
[0023] C1. Disperse paper pulp in distilled water, and add sodium bromide, sodium hypochlorite and TEMPO in sequence under stirring; during the process, the pH is maintained between 10.2 and 11 by dropping sodium hydroxide solution; the oxidation reaction is continued for 12 to 18 hours; wherein the mass ratio of paper pulp, sodium bromide, sodium hypochlorite and TEMPO is 1:(0.09-0.11):(3.1-3.15):(0.015-0.017).
[0024] C2. Separating the solid after the reaction, washing with deionized water, and dialyzing to obtain nanocellulose with an aspect ratio between 109.6 and 170.1.
[0025] A heavy metal adsorption and detection dual-functional fluorescent cellulose-based hydrogel is used as an adsorbent and / or detector in wastewater treatment.
[0026] Advantages of the present invention: The heavy metal adsorption and detection dual-functional fluorescent cellulose-based hydrogel of the present invention can achieve efficient detection and adsorption of Cu(II) and Cr(VI), and has great potential in treating harmful metals in wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is the hydrogen nuclear magnetic resonance spectrum of the intermediate compound M in Preparation Example 2;
[0028] Figure 2 is the carbon NMR spectrum of the intermediate compound M of Preparation Example 2;
[0029] Figure 3 is the mass spectrum of the intermediate compound M of Preparation Example 2;
[0030] Figure 4 is the nuclear magnetic resonance hydrogen spectrum of the fluorescent probe W of Preparation Example 3;
[0031] Figure 5 is the carbon NMR spectrum of the fluorescent probe W of Preparation Example 3;
[0032] Figure 6 is the mass spectrum of the fluorescent probe W of Preparation Example 3;
[0033] Figure 7 is a transmission electron microscope image of the nanocellulose CNF of manufacturing example 1;
[0034] Figure 8 This is the SEM analysis image of PAA-CNF-W of Example 4;
[0035] Fig. 9 This is the EDS analysis diagram of PAA-CNF-W of Example 4;
[0036] Fig.10 FTIR analysis charts of CNF of Manufacturing Example 1, W of Manufacturing Example 3, PAA-CNF-W of Example 4, and PAA hydrogel of Comparative Example 3;
[0037] Fig.11 FTIR comparison chart of PAA-CNF-W hydrogel without adsorption, PAA-CNF-W hydrogel with adsorption of Cu(II), and PAA-CNF-W hydrogel with adsorption of Cr(VI) in Example 4;
[0038] Fig.12 The XPS spectra of C, O, and N of PAA-CNF-W of Example 4;
[0039] Fig.13 is a swelling ratio curve of PAA-CNF-W of Example 4;
[0040] Fig.14 This is a 10-cycle compression test curve of PAA-CNF-W of Example 4 at 60% strain;
[0041] Fig.15 It is a comparison diagram of the compression test curves of the PAA-CNF-W hydrogels of Examples 1 to 4 and the fluorescent hydrogel of Comparative Example 1 with different CNF contents under 60% strain;
[0042] Fig.16 This is a comparison of fluorescence images of the PAA-CNF-W hydrogel of Example 4 immersed in different metal ion solutions;
[0043] Fig.17 This is a comparison diagram of the fluorescence intensity of PAA-CNF-W in Example 4 under the action of different metal ions;
[0044] Fig.18 is the relationship curve between the fluorescence intensity of PAA-CNF-W and the Cu(II) concentration in Example 4;
[0045] Fig.19 is a curve showing the relationship between the fluorescence intensity of PAA-CNF-W and the Cr(VI) concentration in Example 4;
[0046] Fig. 20 This is a comparison chart of the minimum detection limits of Cu(II) for PAA-CNF-W hydrogels of Examples 1 to 4 and the fluorescent hydrogel of Comparative Example 1;
[0047] Fig.21 This is a comparison chart of the minimum detection limits of Cr(VI) for the PAA-CNF-W hydrogels of Examples 1 to 4 and the fluorescent hydrogel of Comparative Example 1;
[0048] Fig. 22 The adsorption curves of Cu(Ⅱ) and Cr(Ⅵ) by the PAA-CNF-W hydrogel of Example 4 at different times;
[0049] Fig.23 The adsorption curves of Cu(Ⅱ) and Cr(Ⅵ) by the pure PAA hydrogel of Comparative Example 3 at different times;
[0050] Fig.24 This is a comparison chart of the adsorption amounts of Cu(II) and Cr(VI) by the PAA-CNF-W hydrogels of Examples 1 to 4 and the fluorescent hydrogel of Comparative Example 1 under equilibrium conditions. DETAILED DESCRIPTION
[0051] In order to deepen the understanding of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. The embodiments are only used to explain the present invention and do not limit the protection scope of the present invention.
[0052] Materials preparation:
[0053] 2,2,6,6-Tetramethylpiperidin-1-oxyl (TEMPO), diethyl iminodiacetate, dansyl chloride, 4-dimethylaminopyridine (DMAP), N,N′-methylenebisacrylamide (MBA), 2,2′-azobisisobutylamidine dihydrochloride (AAPH) and acrylic acid (AA) were purchased from MacLean Company (Shanghai, China).
[0054] Ethyl acetate, tetrahydrofuran, ammonium chloride, anhydrous sodium sulfate, anhydrous ethanol, n-hexane, hydrochloric acid, sodium bromide, and sodium hydroxide (NaOH) were purchased from Sinopharm Chemical Reagent (Shanghai, China).
[0055] Sodium hypochlorite solution (NaClO) was purchased from Guangzhou Chemical Reagent (Guangzhou, China).
[0056] Preparation Example 1 Preparation of Nanocellulose (CNF):
[0057] 4 g of bleached Kraft softwood pulp was dispersed in 400 mL of distilled water. Under magnetic stirring, sodium bromide (0.4 g), sodium hypochlorite (12.5 g) and TEMPO (0.064 g) were added in sequence. During this period, sodium hydroxide solution was added dropwise to keep the pH between 10.2 and 11, and the oxidation reaction lasted for 12 hours. The oxidized solid was diluted with deionized water and washed, then dialyzed for 7 days to obtain a fibrous cellulose solid residue, and then the obtained fibrous cellulose solid residue was dispersed by ultrasonic for 30 minutes to obtain nanocellulose (CNF) with an aspect ratio of 109.6-170.1. Figure 7TEM image of a CNF sample separated from bleached Kraft softwood pulp (scale bar = 2 μm).
[0058] Preparation Example 2 Preparation of fluorescent probe intermediate compound (M):
[0059] DMAP (366.0 mg) was added to a flask containing tetrahydrofuran (15 mL), followed by diethyl iminodiacetate (416.0 mg). Dansyl chloride (539.5 mg) was then dissolved in ethyl acetate (5 mL) and poured into the above solution. The reaction mixture was stirred at room temperature for 16 hours. Then, a saturated solution of ammonium chloride (5 mL) and water (20 mL) was added to quench. The organic phase was separated, the aqueous phase was extracted with ethyl acetate (10 mL × 3), the organic phase was combined, dried over anhydrous sodium sulfate, and concentrated under reduced pressure. The residue was purified by flash chromatography on silica gel (ethyl acetate / n-hexane = 1:3) to give intermediate compound (M) (yellow solid particles, 1.68 mmol, yield 84%).
[0060] The molecular formula of the intermediate compound M is C 20 H 26 O6N2S; the structural formula is as follows:
[0061]
[0062] The H NMR spectrum of the intermediate compound M is as follows Figure 1 As shown, the carbon NMR spectrum is Figure 2 As shown, the mass spectrum Figure 3 As shown, the synthesis of intermediate compound M can be demonstrated.
[0063] The NMR data of intermediate compound M are as follows:
[0064] 1 H NMR(CDCl3,400MHz): δ8.54-8.46(m,1H),8.36-8.20(m,2H),7.58-7.46(m,2H),7.26 -7.12(m,1H),4.31(s,4H),4.00(q,J=7.2Hz,4H),2.87(s,6H),1.10(t,J=7.2Hz,3H).
[0065] 13 C NMR(CDCl3,100MHz): δ168.67(2C),151.66,134.96,130.47,129.95,129.87,129. 17,128.01,123.06,119.29,115.16,61.26(2C),48.14(2C),45.3(2C),13.83(2C).
[0066] Preparation Example 3 Preparation of fluorescent probe (W):
[0067] In a 50 mL flask, intermediate compound M (1.5 mmol) and ethanol (7.5 mL) were added; the mixture was stirred at 55°C, and at the same time, an aqueous solution (7.5 mL) of sodium hydroxide (15 mmol) was gradually added dropwise; the color of the mixture changed from yellow to red and finally to dark red. Then, the ethanol was removed by a rotary evaporator, and then acidified with a dilute hydrochloric acid solution (3 mol / L) until pH = 3 to precipitate the product, and the solid product was further filtered and dried under vacuum to obtain a fluorescent probe (W) (1.23 mmol, yield 82%); the yield was calculated based on the weight difference.
[0068] The molecular formula of fluorescent probe W is C 16 H 17 N2O6S; the structural formula is as follows:
[0069]
[0070] The H NMR spectrum of the fluorescent probe W is shown in Figure 4 As shown, the carbon NMR spectrum is Figure 5 As shown, the mass spectrum Figure 6 As shown, the synthesis of fluorescent probe W can be demonstrated.
[0071] The NMR data of fluorescent probe W are as follows:
[0072] 1 H NMR(DMSO-d6,400MHz): δ12.91(br s,2H),8.48-8.40(m,1H),8.30-8.26(m,1H),8.20-8.16(m,1H),7.64-7.56(m,2H),7.28-7.20(m,1H),4.18(s,4H),2.81(s,6H).
[0073] 13 C NMR (DMSO-d6, 100MHz): δ170.13(2C),151.37,135.68,129.58,129.34,129.22,128.3,128.07,123.58,119,115.2,48.46(2C),45.09(2C).
[0074] Example 1
[0075] Preparation of fluorescent cellulose-based hydrogel (PAA-CNF-W):
[0076] The CNF of manufacturing example 1 was dissolved in a sodium hydroxide solution (1 mol / L) and uniformly dispersed by ultrasonic treatment; then AA, MBA, AAPH and W from manufacturing example 3 were added to the mixed solution and stirred continuously for 2 hours; finally, the mixed solution was poured into a mold, heated at 60°C for 3 hours, and the product was immersed in distilled water to remove the residual reagents to obtain a fluorescent cellulose-based hydrogel (PAA-CNF-W). Among them, the fluorescent cellulose-based hydrogel contains 0.05% CNF, 0.67% W, and the rest acrylic acid hydrogel by mass percentage; the mass ratio of AA, MBA, and AAPH is 1:0.1:0.15.
[0077] Example 2
[0078] The difference between this embodiment and embodiment 1 is that the fluorescent cellulose-based hydrogel contains 0.1% CNF, 0.67% W, and the remainder acrylic acid hydrogel by mass percentage. The rest is the same as embodiment 1.
[0079] Example 3
[0080] The difference between this embodiment and embodiment 1 is that the fluorescent cellulose-based hydrogel contains 0.15% CNF, 0.67% W, and the remainder acrylic acid hydrogel by mass percentage. The rest is the same as embodiment 1.
[0081] Example 4
[0082] The difference between this embodiment and embodiment 1 is that the fluorescent cellulose-based hydrogel contains 0.2% CNF, 0.67% W, and the remainder acrylic acid hydrogel by mass percentage. The rest is the same as embodiment 1.
[0083] Comparative Example 1
[0084] The difference between this comparative example and Example 1 is that no CNF is added. The rest is the same as Example 1. A fluorescent hydrogel without CNF is obtained. Specifically: AA, MBA, AAPH and W are added to a sodium hydroxide solution (1 mol / L) and stirred continuously for 2 hours; finally, the mixed solution is poured into a mold, heated at 60°C for 3 hours, and the product is immersed in distilled water to remove the residual reagents to obtain a fluorescent hydrogel. Among them, the fluorescent hydrogel contains 0.67% W and the rest acrylic hydrogel by mass percentage; the mass ratio of AA, MBA and AAPH is 1:0.1:0.15.
[0085] Comparative Example 2
[0086] In this comparative example, 0.3% CNF was added relative to Example 1. Other aspects were the same as Example 1. In this comparative example, CNF could not be dissolved well after ultrasound treatment, and floccules were generated, which affected the synthesis of the hydrogel.
[0087] Comparative Example 3
[0088] This comparative example is the preparation of pure PAA hydrogel, specifically: AA, MBA, and AAPH were added to a sodium hydroxide solution (1 mol / L) and stirred continuously for 2 hours; finally, the mixed solution was poured into a mold, heated at 60°C for 3 hours, and the product was immersed in distilled water to remove the residual reagents to obtain pure PAA hydrogel. The mass ratio of AA, MBA, and AAPH was 1:0.1:0.15.
[0089] The PAA-CNF-W of Example 4 was subjected to SEM analysis; Figure 8 As shown, Figure 8 is the SEM structure of PAA-CNF-W (scale bar = 6 μm); Figure 8 It can be clearly observed that the cross-section of the hydrogel has a rich pore structure and is evenly distributed on the interface of the hydrogel; CNF can be observed in the cavity, and CNF provides a three-dimensional network structure and active sites, which is beneficial to the adsorption of metal ions by PAA-CNF-W hydrogel.
[0090] The PAA-CNF-W of Example 4 was subjected to EDS analysis; Fig. 9 As shown, Fig. 9 This is the EDS analysis diagram of PAA-CNF-W. Fig. 9 It can be clearly observed that carbon (C), oxygen (O), sulfur (S), and nitrogen (N) elements are evenly distributed, indicating that the fluorescent probe and cellulose are dispersed in the PAA-CNF-W hydrogel.
[0091] Infrared (FTIR) analysis was performed on CNF, W, PAA-CNF-W of Example 4 and pure PAA hydrogel of Comparative Example 3; Fig.10 As shown, Fig.10 This is the FTIR analysis of PAA-CNF-W. -1 FTIR spectra were collected in the range to identify the functional groups in the hydrogel. Fig.10 It can be clearly observed that when CNF is added, PAA is noticed at 3480 cm -1 The OH stretching vibration peak further red-shifts to 3408 cm -1 (such as PAA-CNF-W), while PAA-CNF-W is at 3680-3000cm -1 The stretching vibration of OH at 1600 cm-1 is significantly reduced compared with that of pristine PAA, indicating the interaction between the carboxyl groups in PAA and the hydroxyl groups on CNF. -1The characteristic peak of CNF completely changes to 1704 cm -1 In addition, the 1238 cm -1 The absorption peak at 1047cm -1 The stretching vibration of CNF characteristic peak CO was observed at 1378, 1456, and 1570 cm -1 The absorption bands at 895 cm-1 are attributed to the stretching of S=O and the bending of C=C in the naphthalene unit. -1 The absorption peak at is due to the β-glycosidic bond between CNF and PAA-CNF-W, which does not exist in the fluorescent probe. The characteristic absorption peaks of the fluorescent probe and CNF were observed in the PAA-CNF-W hydrogel, indicating that both were successfully incorporated into the interior of the PAA-CNF-W hydrogel. The addition of CNF and fluorescent probe gave PAA-CNF-W adsorption and detection capabilities.
[0092] The PAA-CNF-W of Example 4 was then subjected to infrared (FTIR) analysis before adsorption, after adsorption of Cu(II), and after adsorption of Cr(VI); Fig.11 As shown, Fig.11 This is the FTIR comparison diagram of PAA-CNF-W hydrogel and PAA-CNF-W hydrogel after adsorption of Cu(Ⅱ) and Cr(Ⅵ). Fig.11 It can be clearly observed that after PAA-CNF-W adsorbs Cu(Ⅱ) and Cr(Ⅵ), the -1 The pyranose ring band at 3600-3000 cm -1 The broadband intensity at 1700 cm-1 decreased significantly after adsorption, indicating that OH participated in the adsorption. -1 The C=O stretching vibration band at 902 cm-1 is reduced, indicating that the carboxyl group is also an adsorption site for Cu(Ⅱ) and Cr(VI). -1 and 759cm -1 The typical bands belong to asymmetric Cr-O stretching and asymmetric Cr-O-Cr bridge vibration. The above FTIR analysis results show that PAA-CNF-W has obvious enrichment and adsorption effects on Cu(Ⅱ) and Cr(Ⅵ).
[0093] XPS analysis was performed on PAA-CNF-W of Example 4; Fig.12 As shown, Fig.12 The XPS spectra of C, O, and N of PAA-CNF-W. Fig.12It was clearly observed that PAA-CNF-W contained a small amount of nitrogen, indicating that the fluorescent probe W was successfully introduced into the hydrogel.
[0094] The swelling rate of PAA-CNF-W in Example 4 was tested; Fig.13 As shown, Fig.13 The swelling rate curve of PAA-CNF-W is shown in Figure 2. Fig.13 It is clearly observed that PAA-CNF-W has good swelling properties, about 1350%, which has a good promoting effect on subsequent adsorption.
[0095] The mechanical strength of PAA-CNF-W in Example 4 was tested; Fig.14 As shown, Fig.14 This is a 10-cycle compression test of PAA-CNF-W at 60% strain; the compressive strength of PAA-CNF-W is 424 kPa. This is due to the addition of cellulose, which provides a skeleton and a three-dimensional network, giving the hydrogel excellent mechanical properties and swelling properties.
[0096] The mechanical strength of PAA-CNF-W of Examples 1-4 and the fluorescent hydrogel of Comparative Example 1 were tested and compared; Fig.15 As shown, Fig.15 A compression test of PAA-CNF-W with different CNF contents at 60% strain;
[0097] When the mass percentage content of CNF is 0% (Comparative Example 1), the compressive strength of the hydrogel is 152 kPa;
[0098] When the mass percentage content of CNF is 0.05% (Example 1), the compressive strength of the hydrogel is 181 kPa;
[0099] When the CNF mass percentage content is 0.1% (Example 2), the compressive strength of the hydrogel is 208 kPa;
[0100] When the mass percentage content of CNF is 0.15% (Example 3), the compressive strength of the hydrogel is 375 kPa;
[0101] When the CNF mass percentage content is 0.2% (Example 4), the compressive strength of the hydrogel is 424 kPa;
[0102] From the comparison of the above mechanical strength test, CNF-enhanced hydrogels showed significantly higher compression performance, especially when the CNF content increased to 0.2%. It should also be noted that in this test, the hydrogel with a CNF mass percentage of 0.3% in Comparative Example 2 was not tested. This is because during the preparation process of the hydrogel, CNF was not completely dissolved and flocs were produced, which affected the subsequent synthesis of the hydrogel. The resulting hydrogel was fragile and had very poor toughness, which affected its mechanical properties and was not conducive to repeated use.
[0103] The PAA-CNF-W of Example 4 was tested for metal ion selective detection; Fig.16 and Fig.17 As shown, Fig.16 PAA-CNF-W hydrogel was immersed in different metal ion solutions (Ca 2+ , Pb 2+ 、Cd 2+ 、Na + , Ba 2+ , Fe 3+ Cr 3+ 、Co 2+ , K + , Li + Mg 2+ 、Ni 2+ 、Zn 2+ , Cu 2+ Cr 6+ ) after . Fig.17 Figure 2 is the fluorescence intensity spectrum of PAA-CNF-W hydrogel under the action of metal ions. Fig.16 and Fig.17 It can be clearly observed that Cr(VI) and Cu(II) can cause obvious fluorescence quenching, while other metal ions, especially Fe in traditional spectrophotometry, 3+ The fluorescence effect of interfering ions such as ions on PAA-CNF-W hydrogel and fluorescent probe W is weak. The results show that PAA-CNF-W hydrogel has a good selective detection effect on Cr(VI) and Cu(II). 3+ The fluorescence effect is also very weak, which can effectively distinguish Cr(III) and Cr(VI) with different toxicities to prevent false positive detection results.
[0104] The PAA-CNF-W of Example 4 was tested for Cu(II) detection performance; Fig.18 As shown, Fig.18 The relationship curves between fluorescence intensity and Cu(Ⅱ) concentration are shown in Figure 2. Fig.18 It can be clearly observed that there is a good linear relationship between Cu(Ⅱ) concentration and fluorescence quenching efficiency ((F0-F) / F0) (R2 =0.99333)(F0 is the initial fluorescence intensity of the sample, and F is the fluorescence intensity of the sample in different concentrations of metal ion solutions). The detection limit (LOD) of PAA-CNF-W hydrogel for Cu(Ⅱ) is about 29μg / L in a wide concentration range of 100-1400μg / L and a signal-to-noise ratio of 3; the photo on the right side of the curve shows the fluorescence intensity comparison of PAA-CNF-W hydrogel at different Cu(Ⅱ) concentrations.
[0105] The Cr(VI) detection performance of PAA-CNF-W of Example 4 was tested; Fig.19 As shown, Fig.19 The relationship curves between fluorescence intensity and Cr(VI) concentration are shown in Figure 2. Fig.19 It can be clearly observed that with the increase of Cr(VI) concentration, the fluorescence of PAA-CNF-W hydrogel is gradually quenched. When the Cr(VI) concentration is 80 μg / L, it is completely quenched.
[0106] pass Fig.18 and Fig.19 Compared with Cu(Ⅱ), Cr(VI) has a greater quenching effect on the hydrogel and emits rapid fluorescence quenching in a narrow concentration range. As the concentration of Cr(VI) increases from 5μg / L to 80μg / L, the quenching effect increases linearly (R 2 =0.99556, LOD = 0.5 μg / L), which has a lower detection limit than the national standard GB / T 7467.
[0107] The detection limits of PAA-CNF-W of Examples 1-4 and the fluorescent hydrogel of Comparative Example 1 for Cu(II) were compared; Fig. 20 As shown,
[0108] The detection limit of the fluorescent hydrogel of Comparative Example 1 for Cu(Ⅱ) is 47.2 μg / L;
[0109] The detection limit of PAA-CNF-W of Example 1 for Cu(II) is 43.7 μg / L;
[0110] The detection limit of PAA-CNF-W of Example 2 for Cu(II) was 39.7 μg / L;
[0111] The detection limit of PAA-CNF-W of Example 3 for Cu(II) was 34.1 μg / L;
[0112] The detection limit of PAA-CNF-W of Example 4 for Cu(II) is 29 μg / L.
[0113] The detection limits of Cr(VI) by PAA-CNF-W of Examples 1-4 and the fluorescent hydrogel of Comparative Example 1 were compared; Fig.21 As shown,
[0114] The detection limit of the fluorescent hydrogel of Comparative Example 1 for Cr(VI) is 4.52 μg / L;
[0115] The detection limit of PAA-CNF-W of Example 1 for Cr(VI) is 3.42 μg / L;
[0116] The detection limit of PAA-CNF-W of Example 2 for Cr(VI) is 2.37 μg / L;
[0117] The detection limit of PAA-CNF-W of Example 3 for Cr(VI) is 1.44 μg / L;
[0118] The detection limit of PAA-CNF-W of Example 4 for Cr(VI) is 0.5 μg / L.
[0119] pass Fig. 20 and Fig.21 From the comparison chart, it can be concluded that as the amount of CNF in the hydrogel gradually increases, the detection limits of Cu(Ⅱ) and Cr(Ⅵ) decrease accordingly, and at 0.2% CNF, the detection limits are 29μg / L and 0.5μg / L, respectively. As the amount of CNF increases, a skeleton supporting the gel is formed, and more adsorption sites are provided, which effectively improves the adsorption capacity of the hydrogel, allowing more metal ions to accumulate on the surface of the hydrogel and enter the interior of the hydrogel. The metal ions have more opportunities to react with the fluorescent probe W therein, which leads to fluorescence quenching.
[0120] The adsorption performance of PAA-CNF-W in Example 4 was tested: After the adsorption test of PAA-CNF-W, the final equilibrium concentration was determined by inductively coupled plasma emission spectroscopy (ICP, PerkinElmer, USA). All experiments were repeated three times. The adsorption amount (q e , mg / g) and the adsorption amount at a certain moment (q t , mg / g) is calculated by the following equation:
[0121] q e =V(C0-C e ) / m
[0122] q t =V(C0-C t ) / m
[0123] Among them, C0, Ce , C t are the initial concentration, equilibrium concentration and concentration at time t (min) of the heavy metal solution, respectively. V (mL) and m (g) are the total volume of the solution and the weight of the PAA-CNF-W hydrogel (oven dried), respectively.
[0124] Reference Fig. 22 As shown, Fig. 22 The adsorption curves of PAA-CNF-W hydrogel for Cu(Ⅱ) and Cr(Ⅵ) at different times. The test was to adsorb the hydrogel in Cu(Ⅱ) (pH=4, 25℃) and Cr(Ⅵ) (pH=2, 25℃) solutions for different times. The initial concentration of the solution was 200μg / L and the volume was 5L. Fig. 22 It can be clearly observed that the adsorption amount of PAA-CNF-W hydrogel gradually increases with the extension of adsorption time. At this time, the maximum adsorption amounts of Cu(Ⅱ) and Cr(Ⅵ) are 6.5 mg / g and 8.3 mg / g, respectively; in addition, the adsorption amounts of Cu(Ⅱ) and Cr(Ⅵ) increase sharply in the first 4 hours, reaching 90% of the maximum adsorption amount. Because the hydrogels initially contain a large number of binding sites, they can quickly bind to water and quickly absorb water and heavy metal ions. After entering the slow stage, the reduction in binding sites leads to a decrease in the adsorption rate, and eventually reaches saturation.
[0125] Refer to Fig.23 As shown, Fig.23 The adsorption curves of Cu(Ⅱ) and Cr(Ⅵ) by the pure PAA hydrogel of comparative example 3 at different times are shown in FIG. Fig. 22 In comparison, the adsorption capacity of Cu(Ⅱ) and Cr(Ⅵ) by PAA-CNF-W was significantly better than that of pure PAA hydrogel at the same time.
[0126] The adsorption of Cu(II) and Cr(VI) by PAA-CNF-W of Examples 1-4 and the fluorescent hydrogel of Comparative Example 1 at equilibrium was compared; Fig.24 As shown,
[0127] The adsorption capacity of Cu(Ⅱ) by the fluorescent hydrogel of Comparative Example 1 at equilibrium state was 3.9 mg / g;
[0128] The adsorption capacity of Cu(II) by PAA-CNF-W pair of Example 1 at equilibrium state was 4.3 mg / g;
[0129] The adsorption capacity of Cu(II) by PAA-CNF-W of Example 2 at equilibrium is 4.9 mg / g;
[0130] The adsorption capacity of Cu(II) by PAA-CNF-W pair of Example 3 at equilibrium state was 5.4 mg / g;
[0131] The adsorption capacity of Cu(II) by PAA-CNF-W of Example 4 at equilibrium state was 6.5 mg / g;
[0132] The adsorption amount of Cr(VI) by the fluorescent hydrogel of Comparative Example 1 at equilibrium is 3.4 mg / g;
[0133] The adsorption capacity of Cr(VI) by the PAA-CNF-W pair of Example 1 at equilibrium is 4.2 mg / g;
[0134] The adsorption amount of Cr(VI) by PAA-CNF-W of Example 2 at equilibrium is 5.3 mg / g;
[0135] The adsorption amount of Cr(VI) by PAA-CNF-W of Example 3 at equilibrium is 6.6 mg / g;
[0136] The adsorption amount of Cr(VI) by PAA-CNF-W of Example 4 at equilibrium is 8.3 mg / g;
[0137] pass Fig.24 It can be seen from the comparison that with the addition of CNF, the adsorption of Cu(Ⅱ) and Cr(Ⅵ) by the hydrogel gradually increases. When the amount of CNF reaches 0.2%, the adsorption of Cu(Ⅱ) and Cr(Ⅵ) reaches 6.5 mg / g and 8.3 mg / g respectively. This is mainly because with the addition of CNF, a three-dimensional network structure and a large number of active sites are provided for the hydrogel. Compared with pure PAA hydrogel, metal ions can more easily enter the interior of the hydrogel through micron-scale three-dimensional channels. At the same time, carboxylated CNF can provide a large number of carboxyl groups, forming a chelation effect with metal ions. At the same time, the negatively charged carboxylated cellulose has a certain electrostatic interaction with metal ions. Chelation and electrostatic effects work together to effectively improve the adsorption effect of the hydrogel.
[0138] In the PAA-CNF-W hydrogel of this embodiment, CNF can adsorb part of Cu(Ⅱ) and Cr(Ⅵ) on the surface of PAA-CNF-W hydrogel through electrostatic interaction. The three-dimensional porous network structure of PAA-CNF-W hydrogel provides abundant ion transport channels and active sites, which promotes the entry of Cu(Ⅱ) and Cr(Ⅵ) into the interior of PAA-CNF-W hydrogel. Cr(Ⅵ) and Cu(Ⅱ) are attached to the porous structure of PAA-CNF-W through electrostatic interaction and complexation. In addition, the fluorescent probe W in PAA-CNF-W hydrogel can be used as a fluorescence source for detecting Cu(Ⅱ) and Cr(Ⅵ). Cu(Ⅱ) and Cr(Ⅵ) are attracted by the fluorescent probe and interact with the fluorescent probe, and the fluorescence is rapidly quenched. In summary, due to these unique structures, the prepared PAA-CNF-W has significant ability to adsorb and detect Cu(Ⅱ) and Cr(Ⅵ).
[0139] The above embodiments should not limit the present invention in any way, and any technical solutions obtained by equivalent replacement or equivalent conversion shall fall within the protection scope of the present invention.
Claims
1. A fluorescent cellulose-based hydrogel with dual functions of heavy metal adsorption and detection, characterized in that: The fluorescent cellulose-based hydrogel contains 0.62%-0.72% of fluorescent probe, 0.05%-0.2% of nanocellulose, and the remainder of acrylic acid hydrogel in terms of mass percentage; Among them, the structural formula of the fluorescent probe is: The nanocellulose is TEMPO-oxidized nanocellulose.
2. The heavy metal adsorption and detection dual-functional fluorescent cellulose-based hydrogel according to claim 1, characterized in that: The fluorescent probe is prepared according to the following steps: A1, dissolving 4-dimethylaminopyridine in tetrahydrofuran, and then adding diethyl iminodiacetate; A2, dissolving dansyl chloride in ethyl acetate, and then adding the whole to the solution obtained in step S1, stirring and reacting at room temperature for about 12-18 hours; wherein the mass ratio of dansyl chloride, diethyl iminodiacetate and 4-dimethylaminopyridine is 1:(0.67-0.78):(0.61-0.72); A3, quenching the reaction, separating and purifying to obtain an intermediate compound; A4. Add the intermediate compound to ethanol, and gradually add sodium hydroxide aqueous solution dropwise at 50-60°C with stirring; the color of the mixture changes from yellow to red and finally to dark red; remove the ethanol, and then acidify with hydrochloric acid solution until the pH is about 3, filter, and dry the obtained solid to complete the preparation of the fluorescent probe; wherein the molar ratio of the intermediate compound to sodium hydroxide is 1:(8-12).
3. The heavy metal adsorption and detection dual-functional fluorescent cellulose-based hydrogel according to claim 2, characterized in that: The reaction quenching of step A3 is performed by adding a saturated aqueous solution of ammonium chloride.
4. A heavy metal adsorption and detection dual-functional fluorescent cellulose-based hydrogel according to claim 2 or 3, characterized in that: The separation in step A3 is as follows: separating the organic phase and extracting the aqueous phase with ethyl acetate; combining the organic phases, drying the organic phases, and concentrating under reduced pressure; the purification in step A3 is as follows: using flash silica gel column chromatography, wherein the mobile phase is a mixture of ethyl acetate and n-hexane in a volume ratio of 1:
3.
5. The heavy metal adsorption and detection dual-functional fluorescent cellulose-based hydrogel according to claim 1, characterized in that: The fluorescent cellulose-based hydrogel is prepared according to the following steps: B1, adding nanocellulose to sodium hydroxide solution for uniform dispersion, and then adding thereto, Add acrylic acid monomer, crosslinking agent, initiator and fluorescent probe, and stir to react for 1.5-2.5h; wherein the mass ratio of acrylic acid monomer, crosslinking agent and initiator is 1:(0.007-0.012):(0.14-0.16); B2. Then, the mixed solution was poured into a mold and reacted at 50-65° C. for 2.5-3.5 h. The reaction product was immersed in distilled water to remove the residual reagents, thereby obtaining a fluorescent cellulose-based hydrogel.
6. The heavy metal adsorption and detection dual-functional fluorescent cellulose-based hydrogel according to claim 5, characterized in that: The cross-linking agent is N,N'-methylenebisacrylamide.
7. A heavy metal adsorption and detection dual-functional fluorescent cellulose-based hydrogel according to claim 5 or 6, characterized in that: The initiator is 2,2'-azobisisobutylamidine dihydrochloride.
8. The heavy metal adsorption and detection dual-functional fluorescent cellulose-based hydrogel according to claim 1, characterized in that: The nanocellulose is prepared according to the following steps: C1. Disperse paper pulp in distilled water, and add sodium bromide, sodium hypochlorite and TEMPO in sequence under stirring; during the process, the pH is maintained between 10.2 and 11 by dropping sodium hydroxide solution; the oxidation reaction is continued for 12 to 18 hours; wherein the mass ratio of paper pulp, sodium bromide, sodium hypochlorite and TEMPO is 1:(0.09-0.11):(3.1-3.15):(0.015-0.017). C2. Separating the solid after the reaction, washing with deionized water, and dialyzing to obtain nanocellulose with an aspect ratio between 109.6 and 170.
1.
9. The use of the heavy metal adsorption and detection dual-function fluorescent cellulose-based hydrogel according to any one of claims 1 to 8, characterized in that: Application as adsorbent and / or detector in wastewater treatment.
Citation Information
Cited By
Rapid detection method for content of key metal impurities in chemical nickel plating layer
CN121762303A
